2005
DOI: 10.1002/j.2050-0416.2005.tb00657.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimising Beer Stabilisation by the Selective Removal of Tannoids and Sensitive Proteins

Abstract: Colloidal stabilisation of all malt and adjunct lager beers through selective removal of haze sensitive glycoproteins using silica gel and tannoid polyphenols using polyvinylpolypyrrolidone (PVPP) or a polyvinylpyrrolidone (PVP)-modified silica gel has been demonstrated during full brewery production. At this scale PVPP and the PVP-modified silica gel exhibited equivalent binding capability for tannoid polyphenols although PVPP removed additional polyphenolic species. Characterisation of proanthocyanidins foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 12 publications
0
18
0
1
Order By: Relevance
“…The tannoid content test correlates with haze-forming polyphenols and colloidal stability better than other tests, e.g., determination of total polyphenols 11 or determination of flavonoids 19 , and provides reliable results in the range between 20-60 mg/L. The disadvantage of the test is that for a tannoid content below 12 mg/L, it gives a zero response, which is a situation typical for beers stabilized by PVPP for colloidal stability of 6 months and more.…”
Section: Introductionmentioning
confidence: 88%
“…The tannoid content test correlates with haze-forming polyphenols and colloidal stability better than other tests, e.g., determination of total polyphenols 11 or determination of flavonoids 19 , and provides reliable results in the range between 20-60 mg/L. The disadvantage of the test is that for a tannoid content below 12 mg/L, it gives a zero response, which is a situation typical for beers stabilized by PVPP for colloidal stability of 6 months and more.…”
Section: Introductionmentioning
confidence: 88%
“…Spektrum jejich vlastností, týkajících se pivovarské technologie a zejména vlastností hotového produktu, je velice široké. V minulosti se studium polyfenolových sloučenin soustřeďovalo zejména na jejich roli v procesu tvorby polyfenol-bílkovinných komplexů, a tím i na vliv polyfenolů na koloidní stabilitu piva (McMurrough et al, 1996a;McMurrough et al, 1996b;Parker, 2007, Aron a Shellhammer, 2010Rehmanji et al, 2005) a možnosti selektivního odstraňování prekursorů vzniku zákalu (Leiper et al, 2005). Po zavedení moderních stabilizačních postupů, schopných odstranit z piva velkou část polyfenolů, byla tato problematika poměrně dlouhou dobu považována za vyřešenou a pozornost se posunula směrem k antioxidačním vlastnostem polyfenolů (Rice-Evans et al, 1996;Pietta, 2000; Dvořáková et al, 2008a), ať už s ohledem na tvorbu senzoricky nežádoucích produktů, zejména karbonylů (Vandehaegen et al, 2006;Mikyška et al, 2011) The aim of this study was to find differences in the quantity and presence of selected polyphenolic substances in barley grown in the Czech Republic and in the People's Republic of China.…”
Section: Porovnání čEských a číNských Odrůd Ječmene S Ohledem Na Techunclassified
“…The range of their properties with regards to beer technology and especially to the quality of the final product is wide. In the past, polyphenols were often studied mainly with regards to their significance in the process of the formation of polyphenols-protein complexes which influence the colloidal stability of beer (McMurrough et al, 1996a;McMurrough et al, 1996b;Parker, 2007;Aron and Shellhammer, 2010;Rehmanji et al, 2005) and to the possible a selective removal of these haze-active precursors from beer (Leiper et al, 2005). This matter was considered as solved with the introduction of modern stabilization methods able to remove a large part of the polyphenols.…”
mentioning
confidence: 99%
“…So the clarity of tea infusion changes, causing the change of light scattering, and the phenomena is called ''tea cream" (Davies, 1998) or ''chill haze" (Peterson, 2003). The driver in haze formation is the complex formation between monomeric or dimeric polyphenols and proteins, to form a larger colloidal particle (Leiper et al, 2005;Rehmanji et al, 2005;McMurrough and O'Rourke, 1997) during storage, it can be observed with a turbidimeter or visually.…”
Section: Introductionmentioning
confidence: 98%